Análise das vibrações e sua relação com o carregamento dos transformadores - Kuriyama, Carlos Sakiti (2022)
In a power electrical system there are a huge number of distribution transformers. They are installed over a very large area, and each unit is considered small power. These characteristics mean that such equipment receives only corrective maintenance. The present dissertation seeks to diagnose the loading condition of transformers by means of low-cost vibration sensors. Two systems were developed to detect transformer vibrations: the first with an MPU6050 accelerometer, a microprocessor and a computer; the second with a MAX9814 microphone, a USB oscilloscope and a computer. The sensors used had features such as low cost, noninvasive installation, and no contact with active parts of the transformer. The experiment used a 400VA three-phase dry-type transformer for the tests. The transformer was submitted to the following loading conditions: empty, with resistive loads and with half wave rectifiers. Observation and analysis of the vibrations in the frequency spectrum was performed. The test highlighted that the main sources of vibration are the windings and the core, and these are related to the loads applied to the transformer. Vibration sensors reduce the cost of monitoring transformers, and thus make the possibility of including transformers in predictive maintenance programs more real.